Unintentional injuries and psychosocial correlates among in-school adolescents in Malaysia - Karl Peltzer (2018)
© 2015 by the authors; licensee MDPI, Basel, Switzerland. The study aimed to provide estimates of the prevalence and psychosocial correlates of unintentional injury among school-going adolescents in Malaysia. Cross-sectional data from the Global School-Based Health Survey (GSHS) included 21,699 students (predominantly ≤13 to ≥17 years) that were selected by a two-stage cluster sample design to represent all secondary school students in Forms 1 to 5. The percentage of school children reporting one or more serious injuries in the past year was 34.9%, 42.1% of boys and 27.8% of girls. The two major causes of the most serious injury were “fall” (9.9%) and motor vehicle accident or being hit by a motor vehicle (5.4%), and the most frequent type of injury sustained was cut, puncture, or stab wound (6.2%) and a broken bone or dislocated joint (4.2%). In multivariable logistic regression analysis, sociodemographic factors (being male and low socioeconomic status), substance use (tobacco and cannabis use), frequent soft drink consumption, attending physical education classes three or more times a week, other risky behavior (truancy, ever having had sex, being bullied), psychological distress, and lack of parental or guardian bonding were associated with annual injury prevalence. Several factors were identified, which could be included in injury prevention promotion programs among secondary school children.